2016
DOI: 10.1016/j.jcf.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk of asthma in heterozygous carriers for cystic fibrosis: A meta-analysis

Abstract: The results show that heterozygous carriers for CF have a higher risk of asthma than non-carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
3
24
3
Order By: Relevance
“…data from bronchial brush samples implicated that the lung pathology in CF is predominated by Th17 and Th1 gene signatures (43), the increased pulmonary presence of the ILC2-activating cytokine IL-33 and augmented levels of the type-2 effector cytokines IL-5, IL-9, and IL-13 in CF BAL and sputum samples as well as the upregulation of local Th2 responses upon chronic infections with Pseudomonas aeruginosa in CF patients strongly argued for a potential, albeit less elucidated, involvement of ILC2s in CF pathogenesis (13,14,42,(44)(45)(46). Accordingly, the risk of asthma, a prototypical ILC2-initiated allergic disease (47), was found to be significantly higher in CF patients compared to non-carriers of a CFTR mutation (48), implicating exaggerated ILC2 activities in CF. In line with this, Cftr −/− mice showed elongated ILC2 responses compared to C57Bl/6 wild type mice upon infection with Aspergillus fumigatus (14).…”
Section: Introductionmentioning
confidence: 99%
“…data from bronchial brush samples implicated that the lung pathology in CF is predominated by Th17 and Th1 gene signatures (43), the increased pulmonary presence of the ILC2-activating cytokine IL-33 and augmented levels of the type-2 effector cytokines IL-5, IL-9, and IL-13 in CF BAL and sputum samples as well as the upregulation of local Th2 responses upon chronic infections with Pseudomonas aeruginosa in CF patients strongly argued for a potential, albeit less elucidated, involvement of ILC2s in CF pathogenesis (13,14,42,(44)(45)(46). Accordingly, the risk of asthma, a prototypical ILC2-initiated allergic disease (47), was found to be significantly higher in CF patients compared to non-carriers of a CFTR mutation (48), implicating exaggerated ILC2 activities in CF. In line with this, Cftr −/− mice showed elongated ILC2 responses compared to C57Bl/6 wild type mice upon infection with Aspergillus fumigatus (14).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CF carriers, having only 1 defective CFTR gene, are not considered to be at increased risk for CF-related conditions (9,10), and CF carriers are routinely informed that they are not at increased health risk (11)(12)(13). However, some studies have found a higher-than-expected proportion of CF carriers with a limited number of CF-related conditions, including congenital bilateral absence of vas deferens (14,15), sinusitis (16)(17)(18), pancreatitis (19)(20)(21), bronchiectasis (22)(23)(24), mycobacterial infections (25)(26)(27), and asthma (23,28). But these investigations generally focused on single conditions, were based on small numbers of patients, did not include controls, and did not compare risk between CF carriers and people with CF.…”
mentioning
confidence: 99%
“…In bronchoalveolar lavage fluid and sputum of patients with CF, the presence of IL-33 as well as IL-5, IL-9 and IL-13 was upregulated, suggesting that local type 2 responses may somehow contribute to CF pathogenesis (100)(101)(102). In line with this, the risk for manifestation of allergic asthma was reported to be higher in patients with CF (103). Morelli et al reported an association of a single nucleotide polymorphism in the IL-9 gene with high Aspergillus-specific IgE levels in females with CF (101).…”
Section: Role Of Ilc2s In Human Fibrotic Lung Diseasesmentioning
confidence: 62%